2019
DOI: 10.1371/journal.pone.0223225
|View full text |Cite
|
Sign up to set email alerts
|

MET as resistance factor for afatinib therapy and motility driver in gastric cancer cells

Abstract: The therapeutic options for advanced gastric cancer are still limited. Several drugs targeting the epidermal growth factor receptor family have been developed. So far, the HER2 antibody trastuzumab is the only drug targeting the HER-family that is available to gastric cancer patients. The pan-HER inhibitor afatinib is currently investigated in clinical trials and shows promising results in cell culture experiments and patient-derived xenograft (PDX) models. However, some cell lines do not respond to afatinib t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The biological roles of CXCL12 also were founded in THCA, in which CXCR4/CXCR7/CXCL12 axis offer new valuable insight into the oncogenesis of metastatic follicular thyroid carcinoma ( Werner et al, 2018 ). The amplification of MET proto-oncogene, receptor tyrosine kinase (MET) is confirmed as a resistance factor in gastric cancer cells ( Ebert et al, 2019 ). And, MET may serve a role in regulating PD-L1 expression in hepatocellular carcinoma ( Chun & Hong, 2019 ) Meanwhile, MET is also involved in high-risk metastasis progression in thyroid cancer ( Garcia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The biological roles of CXCL12 also were founded in THCA, in which CXCR4/CXCR7/CXCL12 axis offer new valuable insight into the oncogenesis of metastatic follicular thyroid carcinoma ( Werner et al, 2018 ). The amplification of MET proto-oncogene, receptor tyrosine kinase (MET) is confirmed as a resistance factor in gastric cancer cells ( Ebert et al, 2019 ). And, MET may serve a role in regulating PD-L1 expression in hepatocellular carcinoma ( Chun & Hong, 2019 ) Meanwhile, MET is also involved in high-risk metastasis progression in thyroid cancer ( Garcia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only cells not undergoing cell division are considered. For a trajectory (x, y, t), 1 ≤ t ≤ N, its approximate average speed is calculated as described earlier [ 17 ]: the approximate average speed is defined as the approximate trajectory length divided by the total elapsed time of the video sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Several mutations in HER2 were reported, which might be associated with trastuzumab resistance [ 8 10 ]. Various RTKs, such as AXL [ 11 ], EGFR [ 12 ], HER3 [ 13 , 14 ] and MET [ 15 17 ] can compensate the inhibition of signaling pathways by anti-HER therapies. Moreover, the downstream signaling pathway can be maintained by genetic alterations, such as mutations of the PI3K catalytic subunit (PIK3CA) or low PTEN expression [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen of 55 PmBs (Table 2) were confirmed by the data of the literature to play certain roles in occurrence and development of GA and were biomarkers or potential therapeutic targets of GA. For example, GPRC5A and SOX9 have been shown to be related to occurrence and development of GA (Liu et al, 2016;, and their expression levels changed more than fourfold in the GA vs. adjacent control samples according to the result of DE RNA analysis (log 2 FC > 2). FCMET has been confirmed as a resistance factor in GA (Ebert et al, 2019), and Wang R. G. et al (2020) demonstrated that FKBP10 may be a crucial player mediating cell proliferation, invasion, and migration by regulating the PI3K signaling pathway in GA. Twenty-seven of 55 PmBs (Table 2) were shown to be associated with other cancers according to the data of the literature. Thus, mRBioM identified some new GA-related mRNAs.…”
Section: Discussionmentioning
confidence: 98%